El juego y la motricidad gruesa en los niños de 4 a 5 años de la escuela de educación básica 25 de Diciembre ubicada en la ciudad de Loja, en el período 2019-2020. - Diaz Soto, Paulina Elizabeth (2021)
The research titled THE GAME AND THE GROSS MOTOR SKILLS IN 4–TO-5-YEAROLD CHILDREN OF THE 25 DE DICIEMBRE ELEMENTARY SCHOOL LOCATED IN THE CITY OF LOJA, IN THE 2019 – 2020 PERIOD; it had, as a general objective, to analyze the importance of games in the gross motor skills in 4–to-5-year-old children, the research's design its non-experimental, with mixed approach and descriptive scope, the used methods were analytical-synthetical and deductive-inductive, to establish the diagnose, a total of 23 people, 22 children and 1 teacher were worked with, taking into account the nonprobability sampling. The technique used was an interview directed to the teacher, the applied instrument to get diagnosis and research within the gross motor area was the Development Abbreviated Scale (EAD-1) by Nelson Ortiz since the population failed in most of the items applied within this area, reason that leads to carry out the investigation in the diagnosed problem, showing that 64% of the population was in a middle level and was alert presenting difficulties at the moment of walking in tiptoes, taking three or more steps, bouncing and grabbing a ball, skipping a 25 cm rope, alternating feet when doing the horselike exercise and, jumping from a 60 cm height. Therefore, designing a games guide was seen as convenient in order to strengthen the children's gross motor skills to propitiate a better development in personal, scholar and social levels.